A study on the effectiveness of sales promotions as a promotional strategy on visitors of A'Famosa Animal World Safari, Alor Gajah, Malacca - Alias, Haslinda (2002)
The research has been conducted at A’Famosa Animal World Safari. A’Famosa Animal World Safari is one of the A’Famosa Resort subsidiary which involved in safari world of entertainment and animal shows. Even though A’FAWS is an interesting place to visit, number of visitors are not as they expected and they can not generate profit out of it. Therefore, the main objective of the study is to identify the effective sales promotional tools to be implement by A’Famosa Animal World Safari as a promotional strategies in order to increase the number of visitors to A’Famosa Animal World Safari. To ensure the success of this research, primary and secondary data collection method is applied. Primary data was gathered through 60 sets of questionnaire that has been distributed at random to the visitors of A’Famosa Resort and A’Famosa Animal World Safari. While secondary data are gathered from various sources, which are internal and external secondary data. Then data are processed by using Statistical Package for Social Science (SPSS) program. Generally, the conclusion of this study are the outcome from the survey analysis, findings and recommendations given by the respondents. Upon the findings, it is found out that promotional strategies currently done are still not reached the optimum level, and A’Famosa Animal World Safari need to be improve its promotion strategies. In recommendation, A’Famosa Animal World Safari needs to improved or develop new promotional strategy especially in sales promotion in order to induce visitors to visit the park. This can be done by make some improvements especially in terms of sales promotion and advertising media as a means to communicate the sales promotion to the potential tourist. Hopefully, by implementing the recommendations, A’Famosa Animal World Safari will become successful in safari world of entertainment and animals shows and well-known not only in Malaysia and through out the world.